2017
DOI: 10.1177/1076029617706756
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Bridging With Low-Molecular-Weight Heparin During Temporary Interruptions of Warfarin: A Register-Based Cohort Study

Abstract: Low-molecular-weight heparin (LMWH) is often recommended as a bridging therapy during temporary interruptions in warfarin treatment, despite lack of evidence. The aim of this study was to see whether we could find benefit from LMWH bridging. We studied all planned interruptions of warfarin within the Swedish anticoagulation register Auricula during 2006 to 2011. Lowmolecular-weight heparin bridging was compared to nonbridging (control) after propensity score matching. Complications were identified in national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…[8][9][10][11] Notable studies included the recent 2017 article by Sjögren et al, a register-based cohort study, which focused on post-warfarin cessation all-cause mortality, bleeding, and thrombosis. 12 However, in this study, the type of procedure that prompted bridging was not known, limiting the generalizability of results. Also of mention, Steinberg et al analyzed results from the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation (ORBIT-AF), a prospective, observational registry study, and found that periprocedural bridging was associated with a higher occurrence of adverse events.…”
Section: Related Literaturementioning
confidence: 89%
“…[8][9][10][11] Notable studies included the recent 2017 article by Sjögren et al, a register-based cohort study, which focused on post-warfarin cessation all-cause mortality, bleeding, and thrombosis. 12 However, in this study, the type of procedure that prompted bridging was not known, limiting the generalizability of results. Also of mention, Steinberg et al analyzed results from the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation (ORBIT-AF), a prospective, observational registry study, and found that periprocedural bridging was associated with a higher occurrence of adverse events.…”
Section: Related Literaturementioning
confidence: 89%
“…We also conducted pre-specified sensitivity analyses excluding conference abstracts or small studies (<100 procedures). Additional (not prespecified) sensitivity analyses were conducted: 1) excluding studies that did not specifically report outcomes for patients with prior venous thromboembolism, but could be included because no study patient experienced an outcome event, and 2) excluding a study 18 that used propensity score matching and weighting to equalize the number of patients in the exposure groups.…”
Section: Data Synthesis and Analysesmentioning
confidence: 99%
“…studies reported results that were unadjusted for potential confounding except for Sjögren et al, 18 where propensity score matching was used.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, less is known about compliance, clinical profile of patients who experienced any events, drug-drug interaction and bridging with heparin in patients treated with warfarin, which is known to increase the risk thromboembolism 27…”
Section: Limitationsmentioning
confidence: 99%